(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Environment is the sum total of an aggregate of all theexternal conditions, forces and circumstances, objects or influence that actupon an organism which live by changing energy and matter with theirenvironment with changing nature of human being environment is not static. Itchanges with corresponding change in time and conditions. It is varied informand physical environment, Biological, Ecological (Edaphic, Diametric, Biotic,Human or Social) Physical and Biological Nature and man made like – Physical,Biological, Social, Economics, Geography, Psychology, Education, Religious,Cultural and Political etc. Theenvironment of an individual comprises the entire physical and social factoraround him, which directly affect his living including the working conditions.The various environmental factors are interdependent and inter weaven with eachother. The Physical environment includes the living and Non living, thegeographical landmark, topography and climatic conditions, the manmade featureslike Buildings, Bridges, Roads, Transports & other Features like health,sanitations, nutrition aspects. Environment isthe sum of the substance and forces externals to the organism in such way thatit affects the organism existence. In relation to man, the environmentconstitutes of air, land, water flora and fauna because these regulates theman’s life.